2010
DOI: 10.1203/pdr.0b013e3181f1c048
|View full text |Cite
|
Sign up to set email alerts
|

Maternal creatine supplementation from mid-pregnancy protects the newborn spiny mouse diaphragm from intrapartum hypoxia-induced damage

Abstract: ABSTRACT:We hypothesized that maternal creatine supplementation from mid-pregnancy would protect the diaphragm of the newborn spiny mouse from the effects of intrapartum hypoxia. Pregnant mice were fed a control or 5% creatine-supplemented diet from mid-gestation. On the day before term, intrapartum hypoxia was induced by isolating the pregnant uterus in a saline bath for 7.5-8 min before releasing and resuscitating the fetuses. Surviving pups were placed with a cross-foster dam, and diaphragm tissue was colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 39 publications
0
26
1
Order By: Relevance
“…We have previously shown that immediately after the 7.5 min asphyxic insult, neonatal spiny mice show evidence of metabolic acidemia (11). Although not measured in this study at 24 h postasphyxia, the increased plasma potassium suggests some continued disruption to metabolic and acid/base homeostasis at this time.…”
Section: Birth Asphyxia Leads To Kidney Damage and Delayed Maturationcontrasting
confidence: 48%
See 1 more Smart Citation
“…We have previously shown that immediately after the 7.5 min asphyxic insult, neonatal spiny mice show evidence of metabolic acidemia (11). Although not measured in this study at 24 h postasphyxia, the increased plasma potassium suggests some continued disruption to metabolic and acid/base homeostasis at this time.…”
Section: Birth Asphyxia Leads To Kidney Damage and Delayed Maturationcontrasting
confidence: 48%
“…Creatine also has the capacity to scavenge free radicals and reduce oxidative stress (10). In our spiny mouse model of birth asphyxia (11)(12)(13), supplementation of the maternal diet with creatine improved survival of the offspring from 60 to 95% (12) and prevented the development of significant brain (13) and muscle deficits (11) observed in the surviving offspring. Of note, we also found that maternal creatine supplementation increased the creatine content of the fetal kidney at term by ~20% (12).…”
mentioning
confidence: 93%
“…In this pathway, the E3 Ub-ligases, muscle-specific ring finger 1 (MuRF1) and muscle atrophy F-box (Atrogin-1/MAFbx), label muscle proteins with poly-ubiquitin (Ub) chains, resulting in their targeted degradation by the 26S-proteasome. The expression of both MuRF and Atrogin-1 are increased during hypoxia [26,27]. The expression of these atrogenes is regulated by inducible transcription factors like NF-kB [28] and Forkhead box O (FOXO).…”
Section: Key Pointsmentioning
confidence: 99%
“…Neurons of the hippocampal Schaffer collateral – Cornu Ammonis (CA) pathway (Capogna, 1998; Geinisman, 2000; Reymann and Frey, 2007), CA1 and CA3 neurons are particularly susceptible to injury caused by global fetal asphyxia at birth, or by cerebral hypoxia‐ischemia [HI] (Kohlhauser et al, 1999; Almli et al, 2000; Loidl et al, 2000; Levin and Godukhin, 2005). Cell loss is not always the primary cause of functional deficits, which can be associated with sub‐cellular changes including in the activation of calcium‐dependent kinases such as calmodulin‐dependent kinase kinase (CaMKK) (Tang et al, 2004; Cannata et al, 2010) and inositol trisphosphate (IP 3 ) and its endoplasmic receptor IP 3 R1 (Nagasawa and Kogure, 1991; Raymond and Redman, 2006; Jurkovicova et al, 2007), and increased expression of trophic proteins such as BDNF (Scheepens et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%